Pengaruh Pajak, Multinasionalitas, dan Tunneling Incentive terhadap Keputusan Transfer Pricing - Rifqiyati Rifqiyati; Masripah Masripah; Munasiron Miftah (Jurnal Akuntansi, Keuangan, dan Manajemen, 2021)
Purpose: This research aimed to determine the effect of taxes, multinationality, and tunneling incentive on the decision on transfer pricing in non-financial sector companies. Research methodology: This research uses quantitative research methods. Testing the hypothesis used multiple linear regression analysis with panel data on Stata 16.0. The population is non-financial sector companies listed on the IDX in 2017-2019. This research has a sample of 53 companies. Results: Based on the results of data analysis, it can be concluded that (1) taxes has a positive and significant effect on the decision on transfer pricing, (2) multinationality has a positive and significant effect on the decision on transfer pricing, (3) tunneling incentive has no effect on the decision on transfer pricing. Limitations: This limitation of research is the number of samples used in this research due to many companies that do not meet the established criteria. Contribution: This study's results can be used as a reference for further researchers and take into consideration for company management, investors and creditors in making decisions.